A hybrid framework for understanding mobile robotic financial service adoption, encompassing utility and trust theories to define service redesign actions. (8th March 2022) - Lin, Shu-Ping; Chan, Ya-Hui; Lu, I-Ying
The mobile robotic financial service (MRFS) is an important disruptive innovation in mobile banking development. However, very few studies have been conducted to investigate MRFS adoption behaviour in order to help define MRFS redesign actions for responding to dynamic markets. Thus, this study's main aims are: 1) to propose a service redesign framework for continuous MFRS innovation; 2) to perform an empirical analysis to explain how to apply it to identify the antecedents of user behaviours, extract determinants, and finally define service redesign actions. Data analysis reveals that the hybrid causal model is partially mediated by extending utility theory to include trust theory. Thus the direct and indirect effects that affect adoption behaviours significantly must be calculated. Finally, action matrix analysis is employed, and the results reveal that the service redesign action changes after the causal dynamics of the hybrid model are considered.